Vulnerabilities in Environment and Health Due to Climate Change and Extreme Hydrological Events: Determinants for Risk Reduction - Chrysanthus, Chukwuma Sr (Journal of Weather Changes, 2025)
This short communication/mini-review immensely emphasizes human health to explicate and elucidate management of the global scourge associated with the determinants and impact of vulnerabilities to extreme hydrologic events and climate change in the absence of risk reduction and their concomitant sequelae. The most effective approach for risk reduction associated with biodiversity, environmental, and health vulnerabilities due to climate change and extreme hydrological events, an ecological framework must take into cognizance exposure, vulnerability, and resilience. This framework emphasizes the significance of understanding the inextricable linkage between ecosystems and human communities are exposed and susceptible to hazards, sensitivity to these hazards, and capacity to cope, adapt and recuperate. Risk reduction incorporates structurally attenuating exposure, strengthening resilience, and sustainably enhancing overall vulnerability management. Extreme weather and climate-associated incidents impinge on human health with consequential morbidity, mortality and socioeconomic challenges and constraints. Climate change and extreme event have altered the frequency, intensity, geographic distribution, and propensity as drivers for change in the future. The indicted variables include hydrological events, such as precipitation, floods and droughts as well as heat waves, wildfires, global warming, extreme temperatures, and hurricanes. The pathways inextricably-linked with extreme events to economic dissipation, human health prognosis and outcomes remain inexplicably diverse and complex; and thus, difficult to predict due to their emergence and reemergence from local, societal and environmental factors which influence disease burden.
Keywords: infectious diseases; morbidity; mortality; agriculture; food security; adaptation; geopolitics; international cooperation; global warming; floods; droughts